SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU (STUDI KASUS DI MTS BERBAUR) - Imroatus Solihah; Abdul Majid; Ahmad Khoiri (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2022)
This study aims to examine the academic supervision of madrasah principals in improving teacher professionalism at MTs BERBAUR. This study uses a qualitative method that is descriptive and analytical. The results of this study: 1) The MTs BERBAUR madrasah principal has implemented POAC (Planning, Organizing, Actuating, and Controlling) management in the academic supervision of the madrasah principal; 2) Academic supervision activities carried out by the madrasah principal have been able to improve the professional competence of teachers at MTs BERBAUR.